Associations between Socio-economic Circumstances at Two Stages of Life and Adolescents’ Oral Health Status - Belinda Nicolau, PhD; Wagner Marcenes, PhD; Me1 Bartley, PhD; Aubrey Sheiham, PhD (Blackwell Synergy, 2005)
There is a consistent association between unfavourable socio-economic circumstances and oral health. Although the effects of poor social circumstances in childhood are known to have lasting influences on general health, there is little information on their effects regarding chronic oral diseases.